Organoids for the Study of Liver Cancer - Wang, Haichuan; Calvisi, Diego F.; Chen, Xin (Seminars in Liver Disease, 2021)
Liver cancer is the second most lethal malignancy worldwide. Cell lines and murine models are the most common tools for modeling human liver carcinogenesis. Most recently, organoids with a three-dimensional structure derived from primary tissues or cells have been applied to liver cancer research. Organoids can be generated from induced pluripotent stem cells, embryonic or adult, healthy or diseased tissues. In particular, liver organoids have been widely employed in mechanistic studies aimed at delineating the molecular pathways responsible for hepatocarcinogenesis. The introduction of clustered regularly interspaced palindromic repeats (CRISPR)-associated protein 9 (Cas9) and microengineered miniorganoid technologies into liver organoids for cancer study has significantly accelerated these investigations. Translational advances have been made by utilizing liver tumor organoids for anticancer drug screening, biobanking, omics profiling, and biomarker discovery. This review summarizes the latest advances and the remaining challenges in the use of organoid models for the study of liver cancer.
Keywords: organoids; primary liver cancer; basic research; translational science